Genetic Study Of Pocket A And B Domain Of RB1 Gene Among Malaysian Children With Retinoblastoma - Ahmad Yusof @ Hanafi, Hanani (2009)
Retinoblastoma (RB) is the most common intraocular tumor mainly affecting children under four years of age, with a prevalence of 1 in 15 000 to 20 000 live births. Retinoblastoma (RB) adalah sejenis kanser mata yang sering terjadi di kalangan kanakkanak yang berumur empat tahun dan ke bawah dengan kekerapan seorang pesakit di kalangan 15,000 hingga 20,000 kelahiran.